2020
DOI: 10.1126/scitranslmed.aay7713
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induces gut microbiota alterations and augments acute graft-versus-host disease after allogeneic stem cell transplantation

Abstract: The efficacy of allogeneic hematopoietic stem cell transplantation (allo-HSCT) is limited by acute and chronic graft-versus-host disease (GVHD). The impact of obesity on allo-HSCT outcomes is poorly understood. Here, we report that obesity had a negative and selective impact on acute gut GVHD after allo-HSCT in mice with diet-induced obesity (DIO). These animals exhibited increased gut permeability, endotoxin translocation across the gut, and radiation-induced gastrointestinal damage after allo-HSCT. After all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…48 Obesity also impacts the microbiome with less diversity being reported. 49,50 Obesity of the recipient has been shown to correlate with poor outcomes after allogeneic HSCT in both mouse preclinical models and human clinical outcome data 50 in which high BMI was associated with a significantly greater risk of grade II-IV acute GVHD 51 (Figure 1). However, there are also clinical studies suggesting that obesity was associated with a higher survival rate after allo-HSCT 52 and auto-HSCT.…”
Section: Significant Differences Between Hsct In Murine Models and Humansmentioning
confidence: 99%
See 4 more Smart Citations
“…48 Obesity also impacts the microbiome with less diversity being reported. 49,50 Obesity of the recipient has been shown to correlate with poor outcomes after allogeneic HSCT in both mouse preclinical models and human clinical outcome data 50 in which high BMI was associated with a significantly greater risk of grade II-IV acute GVHD 51 (Figure 1). However, there are also clinical studies suggesting that obesity was associated with a higher survival rate after allo-HSCT 52 and auto-HSCT.…”
Section: Significant Differences Between Hsct In Murine Models and Humansmentioning
confidence: 99%
“…55 Possible reasons for microbiome shifts in aging could be explained based on diet adjustment, lessened exercise, reduced mobility, residence locations, less muscle mass (sarcopenia), etc. 56 Although obesity and aging correlate with restricted microbiota diversity in mouse and human 50,55,57,58 and the less-diverse microbiome profile has been proved to be associated with poor outcomes after HSCT, [59][60][61] recent studies suggested that there are certain types of bacteria that could serve as beneficial factor for health and longevity. 56,62 Bifidobacteria supplementation reduced the accumulation of aging biomarkers (carbonyls and lipofuscin), 63 while transfer of Christensenella minuta to germ-free mice significantly reduced adiposity gain.…”
Section: Significant Differences Between Hsct In Murine Models and Humansmentioning
confidence: 99%
See 3 more Smart Citations